Design and Build Automatic Cracker Machine Control System Based PLC-Pneumatic - Agus Sifa; Badruzzaman B; A. Sumarudin; Didi Wahyudi (Jurnal Internasional Penelitian Teknologi Terapan, 2022)
Onion crackers are snacks categorized as crackers as complementary foods for the Indonesian people. Crackers are snacks that have a thin, round, and light shape. The process of packaging crackers is partially and fully manually done by humans. Packaging is representative of product quality. The packaging sealing process is influenced by pressure, temperature, and time. The method used in this study is to design and build a control system and test the results of the manufacture, where the control is made based on PLC with CX-Programer software which the system control integrated with HMI made with CX-Designer software. The control system is designed to drive the AC motor of the dosing system, the Dc motor of the packaging puller system, and the vertical and pneumatic heating system on the horizontal sealer system. The control system is made and tested for the function of the I / O program, and the overall control system that has been made works well.